Preparation and Heavy Metal Ions Chelating Properties of Multifunctional Polymer-Grafted Silica Hybrid Materials - Luciana Sartore; Kamol Dey (Advances in Materials Science and Engineering)
In this research work, novel hybrid materials based on multifunctional polymers and silica were developed and investigated in view of possible employment as sorbents for removal of heavy metal ions from water in presence of various ions. Organic-inorganic hybrid materials were prepared by covalent bonding of vinyl-terminated polyamidoamine (PAA) onto aminated silica particles. Two series of polyamidoamine-grafted silica, differing in the PAA chemical structure, were synthesized, and their heavy metal ions chelating properties were investigated. Column adsorption procedure for Cu, Zn, and Ni in aqueous solution was successfully established. Moreover, the adsorption behaviour of the materials was evaluated in different ionic strength solutions as well as in distilled and natural water. Organic-inorganic hybrid materials exhibited excellent chelating properties and selectivity for different metal ions. The hybrid columns showed exceptional eluting and regenerating property using diluted hydrochloric acid solution as eluent. In particular, the hybrid materials containing more carboxy groups possessed superior adsorption ability, reusability, and stability. The consecutive adsorption-desorption experiments exhibited that this material could be reused more than 20 cycles without almost any loss of adsorption capability. These new organic-inorganic sorbents appear very promising as an effective solid-phase extraction material for the selective preconcentration or removing of heavy metal ions from the environment.